Influence of pretreatment of agriculture residues on phytase production by aspergillus niger NCIM 563 under submerged fermentation conditions - Bhavsar, Kavita P.; Shah, Parin; Soni, Sarvesh Kumar; Khire, Jayant Malhar (African Journal of Biotechnology, 2008)
The extracellular phytase production by Aspergillus niger NCIM 563 was evaluated in medium containing various agriculture residues under submerged fermentation conditions. Phytase production was affected by inorganic phosphate content of agriculture residues which ranged from 2.8 to 8 mg/g. The agriculture residues containing less than 4 mg/g inorganic phosphate supported phytase production with maximum activity of 68 IU/ml in medium containing 1% rice bran on 11(th) day of fermentation. Addition of glucose up to 5% in fermentation medium containing 1% rice bran, enhanced phytase production. Pretreatment of agriculture residues with water to remove excess inorganic phosphate has significantly enhanced the phytase activity in case of de-oiled rice bran, wheat bran, peanut cake (low and high oil) and coconut cake. Maximum increase of 20.3 times in phytase activity was observed in case of wheat bran as compared to de-oiled rice bran, coconut cake, peanut cake high and low oil in which the increase in phytase activity was 6.85, 6.1, 5.3 and 3.0 times, respectively. Maximum phytase activity of 68 IU/ml was produced on the 11(th) day of fermentation compared to earlier reported 41.47 IU/ml phytase activity on the 15(th) day of submerged fermentation using 5% dextrin and 2.5% glucose, thus increasing productivity.
Keywords: Agriculture residue; Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation

Strain improvement and up scaling of phytase production by aspergillus niger NCIM 563 under submerged fermentation conditions - Shah, P.; Bhavsar, Kavita P.; Soni, S. K.; Khire, Jayant Malhar (Journal of Industrial Microbiology & Biotechnology, 2009)
Combination of physical and chemical mutagenesis was used to isolate hyper secretory strains of Aspergillus niger NCIM 563 for phytase production. Phytase activity of mutant N-1 and N-79 was about 17 and 47% higher than the parent strain. In shake flask the productivity of phytase in parent, mutant N-1 and N-79 was 6,181, 7,619 and 9,523 IU/L per day, respectively. Up scaling of the fermentation from shake flask to 3 and 14 L New Brunswick fermenter was studied. After optimizing various fermentation parameters like aeration, agitation and carbon source in fermentation medium the fermentation time to achieve highest phytase activity was reduced considerably from 14 days in shake flask to 8 days in 14 L fermenter. Highest phytase activity of 80 IU/ml was obtained in 1% rice bran-3.5% glucose containing medium with aeration 0.2 vvm and agitation 550 rpm at room temperature on 8th day of fermentation. Addition of either bavistin (0.1%), penicillin (0.1%), formalin (0.2%) and sodium chloride (10%) in fermented broth were effective in retaining 100% phytase activity for 8 days at room temperature while these reagents along with methanol (50%) and ethanol (50%) confer 100% stability of phytase activity at 4A degrees C till 20 days. Among various carriers used for application of phytase in feed, wheat bran and rice bran were superior to silica and calcium carbonate. Thermo stabilization studies indicate 100% protection of phytase activity in presence of 12% skim milk at 70A degrees C, which will be useful for its spray drying.
Keywords: Agriculture residue; Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation

High level phytase production by aspergillus niger NCIM 563 in solid state culture: response surface optimization, up-scaling, and its partial characterization - Bhavsar, Kavita P.; Kumar, V. Ravi; Khire, Jayant Malhar (Journal of Industrial Microbiology & Biotechnology, 2011)
Phytase production by Aspergillus niger NCIM 563 was optimized by using wheat bran in solid state fermentation (SSF). An integrated statistical optimization approach involving the combination of Placket-Burman design (PBD) and Box-Behnken design (BBD) was employed. PBD was used to evaluate the effect of 11 variables related to phytase production, and five statistically significant variables, namely, glucose, dextrin, NaNO(3), distilled water, and MgSO(4)center dot 7H(2)O, were selected for further optimization studies. The levels of five variables for maximum phytase production were determined by a BBD. Phytase production improved from 50 IU/g dry moldy bran (DMB) to 154 IU/g DMB indicating 3.08-fold increase after optimization. A simultaneous reduction in fermentation time from 7 to 4 days shows a high productivity of 38,500 IU/kg/day. Scaling up the process in trays gave reproducible phytase production overcoming industrial constraints of practicability and economics. The culture extract also had 133.2, 41.58, and 310.34 IU/g DMB of xylanase, cellulase, and amylase activities, respectively. The partially purified phytase was optimally active at 55A degrees C and pH 6.0. The enzyme retained ca. 75% activity over a wide pH range 2.0-9.5. It also released more inorganic phosphorus from soybean meal in a broad pH range from 2.5 to 6.5 under emulated gastric conditions. Molecular weight of phytase on Sephacryl S-200 was approximately 87 kDa. The K (m) and V (max) observed were 0.156 mM and 220 mu m/min/mg. The SSF phytase from A. niger NCIM 563 offers an economical production capability and its wide pH stability shows its suitability for use in poultry feed.
Keywords: Aspergillus niger; Phytase; Response surface optimization; Solid state fermentation; Statistical methods

Downstream processing of extracellular phytase from aspergillus niger: chromatography process vs. aqueous two phase extraction for its simultaneous partitioning and purification - Bhavsar, Kavita P.; Kumar, V. Ravi; Khire, Jayant Malhar (Process Biochemistry, 2012)
The application of single step aqueous two-phase extraction (ATPE) for the downstream processing of phytase from Aspergillus niger NCIM 563, produced under solid state fermentation, has been studied and compared with the traditional multi-step procedure involving salt precipitation and column chromatography. High phytase recovery (98.5%) within a short time (3 h) and improved thermostability was attained by ATPE in comparison to 20% recovery in 96 h by chromatography process.The ATPE method, therefore, seems to be an interesting alternative for simultaneous partitioning and purification of phytase. The influence of system parameters; such as, phase forming salts, polymer molecular weight and system pH on the partitioning behavior of phytase was evaluated. The ATPE system consisting of combination of polyethylene glycol (PEG) 6000 and 8000(10.5%) and sodium citrate (20.5%) resulted in one-sided partitioning of phytase in bottom phase with a purification factor of 2.5. This is the first report on phytase purification using liquid-liquid extraction and the results are likely to be beneficial in the poultry feed industry. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aspergillus niger; liquid-liquid extraction; Phytase; Polyethylene glycol; Purification

Combinatorial approach of statistical optimization and mutagenesis for improved production of acidic phytase by Aspergillus niger NCIM 563 under submerged fermentation condition - Bhavsar, Kavita P.; Gujar, P.; Shah, P.; Kumar, V. Ravi; Khire, Jayant Malhar (Applied Microbiology and Biotechnology, 2013)
Combination of statistical optimization and mutagenesis to isolate hypersecretory strains is studied to maximize phytase production from Aspergillus niger NCIM 563 under submerged fermentation. The overall results obtained show a remarkable 5.98-fold improvement in phytase production rates when compared to that using basal medium. Optimization of culture conditions from parent strain is studied first by the Plackett-Burman technique to evaluate the effects of 11 variables for phytase production. The results showed that glucose, MgSO4, KCl, incubation period, and MnSO4 are the most significant variables affecting enzyme production. Further optimization in these variables, using a central composite design technique, resulted in 3.74-fold increase in the yield of phytase production to 254,500 U/l when compared with the activity observed with basal media (68,000 U/l) in shake flask. Our experiments show that the phytase from A. niger NCIM 563 exhibits desirable activity in simulated gastric fluid conditions with low pH and also improved thermostability when compared to commercial phytase. The improved yield demonstrates the potential applicability of phytase enzyme as a source of phytase supplement for phosphorus nutrition and environmental protection in animal feed industry. Physical and chemical mutagenesis experiments were carried out in parallel to isolate hypersecretory mutants that could possibly further enhance the enzyme production. Using optimized media conditions of the parent strain, our results show that mutant strain A. niger NCIM 1359 increased the phytase activity by another 1.6-fold to 407,200 U/l.
Keywords: Animal feed; Aspergillus niger; Mutagenesis; Phytase; Statistical optimization

Effect of phytase from aspergillus niger on plant growth and mineral assimilation in wheat (Triticum aestivum Linn.) and its potential for use as a soil amendment - Gujar, Pradnya D.; Bhavsar, Kavita P.; Khire, Jayant Malhar (Journal of the Science of Food and Agriculture, 2013)
Background Extensive use of non-replenishable phosphate reserves as phosphate supplements in agriculture and animal feed poses a threat for environmental pollution and necessitated a search for alternative phosphate sources. Unlocking the phytate phosphorus using microbial phytase can provide an ecofriendly solution in agriculture. The aim of the present work was to evaluate the effect of phytase from Aspergillus niger NCIM 563 in degradation of phytate phosphorus to benefit plant nutrition and soil amendment in comparison with chemical fertilizers. Results An enzyme dose of 12 IU was sufficient to hydrolyze phytate and increase assimilation of phosphorus by about 74%. Phytase supplementation leads to increase in shoot:total length ratio by about 200%, indicating its growth-promoting effect. Consistency in phytase-induced growth was reflected at pot and tray levels, wherein shoot:total length ratio was observed to be 2.01 and 2.12 respectively. Mineral assimilation due to phytase was more efficient as compared to chemical fertilizers, thus overcoming the constraints of practicability and economics in the agriculture industry. Phytase was efficient in reducing the phytic acid content of soil by about 30% while simultaneously increasing the phytate phosphate availability by 1.18-fold. Conclusion Phytase from A. niger showed improvement in phytate phosphorus and mineral availability. Besides a plant growth-promoting effect, reduction in use of chemical fertilizers and soil improvement could be achieved simultaneously for maintaining the sustainability of agriculture. (c) 2012 Society of Chemical Industry
Keywords: mineral assimilation; Phytase; phytate degradation; plant growth promotion; soil amendment

Phytase isozymes from aspergillus niger NCIM 563 under solid state fermentation: biochemical characterization and their correlation with submerged phytases - Bhavsar, Kavita P.; Buddhiwant, Priyanka; Soni, Sarvesh K.; Depan, Dilip; Sarkar, Sampa; Khire, Jayant Malhar (Process Biochemistry, 2013)
Aspergillus niger NCIM 563 produces dissimilar phytase isozymes under solid state and submerged fermentation conditions. Biochemical characterization and applications of phytase Phy III and Phy IV in SSF and their comparison with submerged fermentation Phy I and Phy III were studied. SSF phytases have a higher metabolic potential as compared to SmF. Phy I is tetramer and Phy II, III and IV are monomers. Phy I and IV have pH optima of 2.5 and Phy II and III have pH optima of 5.0 and 5.6, respectively. Phy I, III and IV exhibited very broad substrate specificity while Phy II was more specific for sodium phytate. SSF phytase is less thermostable as compared to SmF phytase. Phy land II show homology with other known phytases while Phy III and IV show no homology with SmF phytases and any other known phytases from the literature suggesting their unique nature. This is the first report about differences among phytase produced under SSF and SmF by A. niger and this study provides basis for explanation of the stability and catalytic differences observed for these enzymes. Exclusive biochemical characteristics and multilevel application of SSF native phytases determine their efficacy and is exceptional. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: A. niger; Isozymes; Phytase; Solid state fermentation; Submerged fermentation

Current research and future perspectives of phytase bioprocessing - Bhavsar, Kavita P.; Khire, Jayant Malhar (RSC Advances, 2014)
Phosphorus is one of nature's paradoxes as it is life's bottleneck for subsistence on earth but at same time is detrimental in surplus quantities in an aquatic environment. Phosphorus cannot be manufactured, though fortunately it can be recovered and reused. The only way to avert a supply crisis is to implement the ``3R's'' of sustainability, ``Reduce, Reuse and Recycle.'' Phytase is likely to play a critical role in the dephosphorylation of antinutritional and indigestible phytate, a phosphorus locking molecule, to digestible phosphorus, calcium and other mineral nutrients in the coming years. Hence, efforts are required to produce cost effective phytase with fast upstream and economic downstream processing because the current available process is expensive and time consuming. This review summarizes the present state of methods studied for phytase bioprocessing. Production, extraction and purification incur a large cost in product development. In addition, the process has several limitations such as dilute concentration of enzyme, extensive downstream procedures and treatment of generated effluents. However, these methods are currently employed due to lack of alternative methods. Thus, there is a clear need for an efficient, scalable and economical process for phytase production and bioseparation, and improvements are especially required with regard to yield, purity, and energy consumption. Perspectives for an improved bioprocess development for phytase are discussed based on our own experience and recent studies. It is argued that the optimization of production techniques, strain improvement and liquid-liquid extraction deserves more attention in the future.